Economics and ethics : an introduction - Dutt, Amitava Krishna; Wilber, Charles K. (Houndsmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2013)
This book analyses the relationship between economics and ethics, explaining how ethics affects individual economic behaviour and the interactions of individuals, and how ethics is important in evaluating the performance of economies.
Includes bibliographical references (pages 263-272) and index.
oif 12/06/15
Loan
Keywords: Economics -- Moral and ethical aspects; Ethics